Altitude-Induced Immunological Changes in Experimental Wound Healing - Kanat, Mamakeev; Esenbai, Abdyshev; Yusup, Umetaliev; Batyrkhan, Niyazov; Taalaibekova, Meerim; Vityala, Yethindra (Trends in Immunotherapy, 2026)
Wound healing is a critical global clinical issue, particularly in surgical and emergency care settings, where infections lead to significant morbidity, extended hospitalization, and increased healthcare costs. This study investigated the impact of altitude deadaptation on immune responses during wound healing in rabbits. Animals with aseptic and purulent wounds were divided into three groups: control (Bishkek), short-term (3-day), and long-term (30-day) high-altitude exposure, followed by descent to Bishkek. Leukocyte profiles and plasma levels of pro-inflammatory interleukin-1 beta (IL-1β) and anti-inflammatory interleukin-10 (IL-10) were analyzed. Short-term high-altitude exposure followed by rapid descent induced a maladaptive immune response characterized by elevated IL-1β levels, peaking at 10.1 ± 0.3 pg/ml on day 1 in aseptic wounds and 31.1 ± 2.5 pg/ml on day 3 in purulent wounds, indicating prolonged inflammation. In contrast, long-term exposure resulted in immune exhaustion, with diminished IL-1β and IL-10 responses. IL-10 levels were disrupted in the short-term exposure group, showing an initial increase followed by a decrease, suggesting inadequate anti-inflammatory effects. Leukocyte counts paralleled cytokine patterns, with initial leukopenia followed by delayed leukocytosis in the short-term exposure group. These findings demonstrate that altitude deadaptation affects immune regulation, inflammation extension, and hinders wound healing.